The saturdays eaudiobook - Enright, Elizabeth (The Melendy Quartet., 2004)
Meet the Melendys! Mona, the eldest, is thirteen. She has decided to become an actress and can recite poetry at the drop of a hat. Rush is twelve and a bit mischievous. Miranda is ten and a half. She loves dancing and painting pictures. Oliver is the youngest. At six, he is a calm and thoughful person. They all live with their father, who is a writer, and Cuffy, their beloved housekeeper, who takes on the many roles of nurse, cook, substitute mother, grandmother, and aunt. Elizabeth Enright's Melendy Quartet captures the lively adventures of this wonderful family as they move from the city to the country!